2007
DOI: 10.1002/aic.11377
|View full text |Cite
|
Sign up to set email alerts
|

A heterogeneous acid‐catalyzed process for biodiesel production from enzyme hydrolyzed fatty acids

Abstract: in Wiley InterScience (www.interscience.wiley.com).In this work, biodiesel synthesis via fatty acids esterification with methanol is conducted by using a heterogeneous catalyst made from cation-exchange resin. The kinetics of esterification is studied at the different levels of catalyst loading (3.65-53.6%, w/w), reaction temperature (333-353 K) and molar ratio of methanol to fatty acids (1:1 to 20:1). The reaction rate and fatty acids conversion increased with increases in catalyst loading, reaction temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Song et al 41 reported a similar result of the temperature effect. The kinetic model was built on the following assumptions: 42,43 (1) The rate of non-catalyzed reactions is negligible compared to that of the catalyzed reations. Under these conditions, the reactions were considered to be second-order in the forward and reverse directions.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al 41 reported a similar result of the temperature effect. The kinetic model was built on the following assumptions: 42,43 (1) The rate of non-catalyzed reactions is negligible compared to that of the catalyzed reations. Under these conditions, the reactions were considered to be second-order in the forward and reverse directions.…”
Section: Resultsmentioning
confidence: 99%
“…The steep increase in CA conversion from 34 to 89% and TBC yield from 6 to 58% with increase in molar ratio from 1:4 to 1:10 was obtained. The higher CA conversion and yield of TBC may be attributed to occupancy of the CA over the active sites present on catalyst surface and the availability of n-butanol molecules for further esterification (Su et al, 2008). Also, at a molar ratio of CA to nbutanol of 1:10, the CA may be chemisorbed on the active sites of catalysts to form carbonium ions.…”
Section: Influence Of Molar Ratio Of Ca To N-butanolmentioning
confidence: 99%
“…The P-H model was found to fit the experimental data fairly well. For example, Su et al used the cation-exchange resin as the acidic catalyst to investigate the esterification kinetics under different conditions (Su et al, 2008). The results showed that the optimal operating condition for obtaining FFAs conversion of 0.99 could be predicted by the P-H kinetic model.…”
Section: Introductionmentioning
confidence: 99%